Debates about African urbanisation, migration and economic growth: what can we learn from Zimbabwe and Zambia?. Issue 3 (14th February 2015) - Potts, Deborah
Abstract : There has been much debate about whether patterns of urbanisation in sub‐Saharan Africa defy the usually accepted links between migration flows and economic geographies. In the 1980s and 1990s African urban economies were weak and increasingly informalised. The livelihoods of the majority of urban households became intensely vulnerable. However, the most widely accepted narrative was that rural–urban migration remained strong and rates of urban growth were unaffected, suggesting that African migrants ignored economic signals and that explanations of migrant behaviour must primarily be non‐economic. A new angle on this debate has now arisen: whether urbanisation in Africa generates economic growth or vice versa. This has been triggered by the much improved GDP growth rates which many African countries have experienced in the twenty‐first century, driven in large part by a commodity boom and increased demand for their natural resources. This paper seeks to contribute to these debates through a detailed analysis of the contrasting experiences of Zimbabwe and Zambia from the 1960s to today. Rates of urbanisation waxed and waned in both and were evidently affected by national economic development patterns which have been highly variable – to a significant extent the experience of each country in each decade has been the mirror image of the other. From this it is argued that, as elsewhere in the world, migration flows have been strongly influenced by economic opportunity. The evidence from these countries also supports the view that it is economic development that drives urbanisation, and not the other way round.